The Bohemians of the Latin Quarter - Murger, Henri, 1822-1861 (Book collections on Project MUSE., 2004)
"Today, as of old, every man who enters on an artistic career, without any other means of livelihood than his art itself, will be forced to walk in the paths of Bohemia."--The PrefaceBased largely upon Henri Murger's own experiences and those of his fellow artists, The Bohemians of the Latin Quarter was originally produced as a play in 1849 and first appeared in book form in 1851. It was an immediate sensation. The novel consists of a series of interrelated episodes in the lives of a group of poor friends-a musician, a poet, a philosopher, a sculptor, and a painter-who attempt to maintain their artistic ideals while struggling for food, shelter, and sex. Set in the ancient Latin Quarter, a vibrant and cosmopolitan area near the University of Paris, the novel is a masterful portrait of nineteenth-century Parisian artistic life. "Bohemian" soon became synonymous with "artist," and it is from Murger's novel that the word and concept entered the English language. Drawn from real-life characters and events, the themes of love, sacrifice, and "selling out" are immediately recognizable to the modern reader. Capturing the heart, spirit, and bittersweet humor of the world of struggling artists, The Bohemians of the Latin Quarter is the universal story of one's attempt to leave a mark on the world